2021
DOI: 10.3390/ijms22083894
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pigmentation-Regulating Agents by Drug Repositioning

Abstract: Skin color is determined by the processes of melanin synthesis and distribution. Problems in various molecules or signaling pathways involved in melanin synthesis contribute to skin pigmentation defects. Several trials have been conducted on the production of pigmentation-regulating agents, and drug repositioning has emerged as a modern technique to identify new uses for existing drugs. Our research team has researched substances or drugs associated with pigmentation control and, as a result, nilotinib, sorafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…α‐MSH binds to melanocortin 1 receptor (MC1R) on melanocytes, which further activates cascade responses of melanin production 1,3 . In addition, UV irradiation also increases the accumulation of melanin in keratinocyte by promoting the melanosome transfer from melanocytes to keratinocyte, mediated through intracellular Ca 2 + accumulation and E‐cadherin 3 . Other melanogenic factors induced by UV irradiation include endothelin‐1, interleukin‐1, granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), SCF, and NGF 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…α‐MSH binds to melanocortin 1 receptor (MC1R) on melanocytes, which further activates cascade responses of melanin production 1,3 . In addition, UV irradiation also increases the accumulation of melanin in keratinocyte by promoting the melanosome transfer from melanocytes to keratinocyte, mediated through intracellular Ca 2 + accumulation and E‐cadherin 3 . Other melanogenic factors induced by UV irradiation include endothelin‐1, interleukin‐1, granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), SCF, and NGF 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted on mouse skin also reported consistent results. The backs of the mice were exposed to UVB with a total energy of 0.5 J/cm 2 . One week before the first UVB irradiation and after the seventh UVB irradiation, BTX‐A was intradermally injected into the mouse skin at a dose of 30 units per kg (approximately 1 unit per 1 cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon exposure to UV radiation, keratinocytes are stimulated to secrete α-MSH, which enhances melanogenesis through multiple pathways related to cAMP, protein kinase A (PKA), cAMP response element-binding protein (CREB), and microphthalmia-associated transcription factor (MITF) activity [6,7]. Several skin-lightening procedures have focused on strategies that inhibit these signals [8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of small compounds that modulate melanogenesis have been reported and are categorized into several groups based on the mechanism of action, cellular signaling [ 4 , 5 ], transcription [ 6 ], translation [ 7 ], cellular trafficking [ 8 ], and degradation [ 9 ]. Post-translational modulators of melanogenic factors are often associated with intracellular trafficking and affect the maturation and fate of melanosomes and related organelles [ 10 ].…”
Section: Introductionmentioning
confidence: 99%